2014
DOI: 10.2174/1570159x11666131120224653
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and Nitrosative Stress and Immune-inflammatory Pathways in Patients with Myalgic Encephalomyelitis (ME)/Chronic Fatigue Syndrome (CFS)

Abstract: Myalgic Encephalomyelitis (ME) / Chronic Fatigue Syndrome (CFS) has been classified as a disease of the central nervous system by the WHO since 1969. Many patients carrying this diagnosis do demonstrate an almost bewildering array of biological abnormalities particularly the presence of oxidative and nitrosative stress (O&NS) and a chronically activated innate immune system. The proposal made herein is that once generated chronically activated O&NS and immune-inflammatory pathways conspire to generate a multit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(146 citation statements)
references
References 293 publications
(304 reference statements)
3
142
0
1
Order By: Relevance
“…In addition, higher peripheral levels of IL-1, IL-6, and TNF-α are also observed in CFS patients compared to healthy controls [20,98] . Finally, CFS (like depression) is accompanied by mitochondrial dysfunction [99] and increased O&NS [100,101] , which play a key role in CFS.…”
Section: Chronic Fatigue Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, higher peripheral levels of IL-1, IL-6, and TNF-α are also observed in CFS patients compared to healthy controls [20,98] . Finally, CFS (like depression) is accompanied by mitochondrial dysfunction [99] and increased O&NS [100,101] , which play a key role in CFS.…”
Section: Chronic Fatigue Syndromementioning
confidence: 99%
“…Furthermore, changes in microbiota composition have been noted in CFS; for instance, levels of Dialister appear to be decreased in CFS [104] , similarly to findings observed in samples with MDD [11] , whereas levels of Alistipes are increased in both diseases, though less consistently so in MDD [11,45,105] . It is noteworthy that CFS frequently co-occurs with IBS, and gut inflammation and endotoxemia may play a patho-etiological role in both diseases [100,106,107] . Similarly to MDD, CFS is characterized by a propensity towards O&NS-induced autoimmune responses [108] .…”
Section: Chronic Fatigue Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms underpinning the detrimental effects of excessive ROS levels on synaptic function are underpinned by oxidation of cytosolic and membrane proteins and peroxidation of membrane lipids [243,244]. For example, several research teams have reported that lipid peroxidation in presynaptic membranes impedes fusion pore opening, thereby restricting SV exocytosis, resulting in the abnormal retention of SVs within presynaptic active zones [245,246].…”
Section: Oxidative Stress and The Development Of Synaptic Dysfunctionmentioning
confidence: 99%
“…The formation of protein carbonyls via the reaction between reactive aldehydes and ketones can function as damage-associated molecular patterns (DAMPS) activating Toll-like receptors (TLRs) in turn activating nuclear factor (NF)-κB and up-regulating the production of proinflammatory cytokines and a plethora of other inflammatory molecules [14,15]. The corruptive effects of unbalanced or excess radical species also lead to adverse changes in macromolecule function and an altered conformation which occasionally renders them immunogenic and an additional source of O&NS and chronic inflammation [16,17]. These and other mechanisms explain why chronic O&NS and chronic inflammation co-exist and self-amplify in a vicious self-sustaining spiral [6,18].…”
Section: Introductionmentioning
confidence: 99%